In situ nanoscale evaluation of pressure-induced changes in structural morphology of phosphonium phosphate ionic liquid at single-asperity contacts. Issue 1 (22nd December 2021) - Li, Zixuan; Morales-Collazo, Oscar; Chrostowski, Robert; Brennecke, Joan F.; Mangolini, Filippo
Abstract : In this work, we perform atomic force microscopy (AFM) experiments to evaluate in situ the dependence of the structural morphology of trihexyltetradecylphosphonium bis(2-ethylhexyl) phosphate ([P6, 6, 6, 14 ][DEHP]) ionic liquid (IL) on applied pressure. Abstract : In this work, we perform atomic force microscopy (AFM) experiments to evaluate in situ the dependence of the structural morphology of trihexyltetradecylphosphonium bis(2-ethylhexyl) phosphate ([P6, 6, 6, 14 ][DEHP]) ionic liquid (IL) on applied pressure. The experimental results obtained upon sliding a diamond-like-carbon-coated silicon AFM tip on mechanically polished steel at an applied pressure up to 5.5 ± 0.3 GPa indicate a structural transition of confined [P6, 6, 6, 14 ][DEHP] molecules. This pressure-induced morphological change of [P6, 6, 6, 14 ][DEHP] IL leads to the generation of a lubricious, solid-like interfacial layer, whose growth rate increases with applied pressure and temperature. The structural variation of [P6, 6, 6, 14 ][DEHP] IL is proposed to derive from the well-ordered layering of the polar groups of ions separated by the apolar tails. These results not only shed new light on the structural organization of phosphonium-based ILs under elevated pressure, but also provide novel insights into the normal pressure-dependent lubrication mechanisms of ILs in general.